Quality of Life, Sexual Health, and Associated Factors Among the Sexually Active Adults in a Metro City of India: An Inquiry During the COVID-19 Pandemic-Related Lockdown - Chatterjee, Seshadri Sekhar; Bhattacharyya, Ranjan; Chakraborty, Amrita; Lahiri, Arista; Dasgupta, Abhijit (Frontiers in Psychiatry, 2022)
Background: Sexual dysfunction(SD) and its effect on our life is an important but less studied topic especially during post-Covid era. This study examines the extent of SD and other mental health predictors and their effect on quality of life. Methods: A cross-sectional survey of sexually active adults was conducted in an Indian metro-city. Along with sociodemographic data, sexual dysfunction, depression, anxiety, stress and quality of Life were assessed by Arizona Sexual Experience Scale (ASEX), Depression Anxiety and Stress Scale (DASS) and WHOQOL-BREF respectively. Structural Equations Modeling was used to understand their relationship. Results: Out of the total 1376 respondents 80.52% were male, 65.98% were married, 48.54% were graduates. The mean age of the participants was 34.42 (± 9.34) years. 27.18% had sexual dysfunction. Majority of the respondents did not have depression (59.30%), anxiety (52.33%) or stress (44.48%). Mild and moderate levels were the commonest findings among those who had depression, anxiety or stress. Among the respondents 27.18% had sexual dysfunction as per the ASEX instrument. Increase in age and female gender were associated with sexual dysfunction overall, and also all its components. Presence of depression adversely affected ease of achieving orgasm and satisfaction from orgasm, and was associated with sexual dysfunction overall. The respondents had a mean score of 73.57 (±13.50) as per the WHO-QOL. Depression and stress emerged as statistically significant factors for poor quality of life, while sexual dysfunction was not associated statistically. Conclusion: More than one-fourth of the study population reported sexual dysfunction during the first wave of the pandemic in India. The study findings highlight the role of poor mental health issues in this regard. In fact, issues like depression and stress were associated with poor quality of life as well. The current findings unequivocally warrant specific interventions to improve mental health of the respondents.